Conceptual Design of Modular Chassis Jig of Student Competition Car - Heryoga Winarbawa (Universitas Sanata Dharma, 2021)
Chassis jig is needed to ensure that the welded chassis components does not warp or deform during welding process. Through concept screening and concept scoring, multiple design of chassis jigs is narrowed down to next development process. This study aims to design a chassis jig for the fabrication of student car competition chassis. The desired result of this design process is chassis jig with the ability to manufacture a wide variety of student competition car chassis.